A case report of anti-GAD65 antibody-positive autoimmune encephalitis in children associated with autoimmune polyendocrine syndrome type-II and literature review - Sapana, Tamang; Li, Wei; Tian, Fengyan; Yan, Wenhao; Dou, Binghua; Hua, Shuang; Zhuo, Zhihong (Frontiers in Immunology, 2023)
Background: Glutamic acid decarboxylase (GAD) is the rate-limiting enzyme for the synthesis of GABA, the major inhibitory neurotransmitter in the CNS. Antibodies against GAD are associated with various neurologic conditions in patients, including stiff person syndrome, cerebellar ataxia, refractory epilepsy, and limbic and extralimbic encephalitis . While there are few case reports and research on anti-GAD65 antibody-associated encephalitis in adults, such cases are extremely rare in pediatric cases . Methods: For the first time, we report a case of anti-GAD65-positive autoimmune encephalitis associated with autoimmune polyendocrine syndrome (APS) type II.We reviewed previously published pediatric cases of anti-GAD65 autoimmune encephalitis to discuss their clinical features, laboratory tests, imaging findings, EEG patterns, and prognosis.An 8-year-old, male child presented to the outpatient department after experiencing generalized convulsions for twenty days. The child was admitted for epilepsy and had received oral sodium valproate (500 mg/day) in another center, where investigations such as USG abdomen and MRI brain revealed no abnormalities, however, abnormal EEG with diffuse mixed activity in the left anterior middle prefrontal temporal region. On the follow-up day, a repeat blood test showed a very low serum concentration of sodium valproate hence the dose was increased to 750 mg/day. Then, the child experienced adverse effects including increased sleep, thirst, and poor appetite, prompting the parents to discontinue the medication. A repeat MRI showed increased signals on FLAIR sequences in the right hippocampus (Fig. 2A) hence admitted for further management. The child's past history included diagnosis of hypothyroidism at the age of 4, and receiving levothyroxine 75 mcg/day. His parents have no history of any similar neurological, autoimmune, or genetic diseases, but his uncle had a history of epilepsy.At presentation, he had uncontrolled blood glucose levels with elevated HbA1c levels. Additionally, the serum and CSF autoantibodies were positive against the anti-GAD65 antibody with the titer of 1:100 and 1:32 respectively. The patient was managed with a mixed type of insulin regimen and received first-line immunotherapy (IVIG) for five consecutive days, followed by oral prednisone and sodium valproate as an antiepileptic drug. Upon achieving a favorable clinical outcome, the patient was discharged with oral medications.